BASIC ANXIETY IN JANE AUSTEN’S PRIDE AND PREJUDICE AND EMMA: Received: 11th April 2024 Revised: 2nd May 2024, 28th May 2024, 29th May 2024, 31st May 2024 Accepted: 11th April 2024 - Hana Djelloul (PEOPLE: International Journal of Social Sciences, 2024)
This paper delves into the inner conflict of Elizabeth Bennet and Emma, the heroines of Jane Austen’s Prejudice and Prejudice and Emma. The study uses Karen Horney’s psychoanalytic social theory of basic anxiety that emphasizes the influence of childhood experiences and the impact of socialization on an individual’s psychological development. It examines certain instances in the heroines’ early experiences that shape their adult identity and self-knowledge. The analysis reveals that those heroines are highly influenced by their parents or chaperones, who themselves may suffer from neurotic struggles that hinder their ability to properly provide care and support for their children. Therefore, an analysis of those parents and chaperones is provided to see to what extent their psychological conflicts preoccupy their behavior towards the heroines.